A false-positive I-131 finding of duodenum diverticulum in thyroid cancer evaluation by SPECT/CT: A case report. Issue 8 (February 2018) - Wang, Rang; Zhou, Ke; Fan, Qiuping; Chen, Haotian; Fan, Chengzhong
Abstract: Rationale: Iodine-131 (I-131) is a sensitive marker for the detection of differentiated thyroid cancer (DTC). I-131 whole-body scintigraphy (WBS) has been used widely in evaluation of DTC patient. However, I-131 WBS exists many false-positive uptake of I-131 because radioiodine uptake can also be seen in healthy tissue or in a variety of benign and malignant non-thyroidal tumors. Patient concerns: A 44-year-old woman with a papillary thyroid carcinoma for the purpose of ablation therapy after a total thyroidectomy. I-131 WBS showed intensive uptake by thyroid remnant. Meanwhile, a focus of increased activity was seen in right upper abdomen. Disgnoses, interventions and outcomes: Based on an I-131 single-photon emission computed tomography/computed tomography (SPECT/CT) fusion imaging combining a Tc-99m pertechnetate dynamic SPECT scan and SPECT/CT fusion imaging with oral administration of iodine contrast agent, a descending duodenum diverticulum was diagnosed. This patient was then treated with conservative treatment, such as diet regulation, rest, appropriate use of antacids and antispasmodic agents, etc. So far, she recovered uneventfully with no any complications. Lessons: Duodenum diverticulum is a rare false-positive uptake of I-131, it might be a diagnostic challenge when there are many false-positive uptake of I-131 in evaluation of DTC. So it must be significant to be familiar with these physiologic and pathologic variants of I-131 uptake and make further efforts to accurately interpret radioiodine scintigraphy results.